An experimental study of plant community invasibility - Burke, M. J. W.; Grime, J. P. (Ecology (Durham), 1996)
A long-term field experiment in limestone grassland near Buxton (North Derbyshire, United Kingdom) was designed to identify plant attributes and vegetation characteristics conducive to successful invasion. Plots containing crossed, continuous gradients of fertilizer addition and disturbance intensity were subjected to a single-seed inoculum comprising a wide range of plant functional types and 54 species not originally present at the site. Several disturbance treatments were applied; these included the creation of gaps of contrasting size and the mowing of the vegetation to different heights and at different times of the year. This paper analyzes the factors controlling the initial phase of the resulting invasions within the plots subject to gap creation. The susceptibility of the indigenous community to invasion was strongly related to the availability of bare ground created, but greatest success occurred where disturbance coincided with eutrophication. Disturbance damage to the indigenous dominants (particularly Festuca ovina) was an important determinant of seedling establishment by the sown invaders. Large seed size was identified as an important characteristic allowing certain species to establish relatively evenly across the productivity-disturbance matrix; smaller-seeded species were more dependent on disturbance for establishment. Successful and unsuccessful invaders were also distinguished to some extent by differences in germination requirements and present geographical distribution.